การพัฒนามาตรวัดความสุขในการเรียนสำหรับนักเรียนมัธยมศึกษาตอนปลาย - สำราญ สิริภคมงคล (จุฬาลงกรณ์มหาวิทยาลัย, 2011)
The purpose of this study was to develop the learning happiness scales for high school students. There were four objectives as follow: 1) to develop indicators and factors of learning happiness for high school students. 2) to develop the learning happiness scale for high school students. 3) to conduct learning happiness scales analysis and exploratory factor analysis were applied in order to determine construct validity and validity of the scale. 4) to construct the norm of learning happiness. The sample were 2,400 high school students from school under the jurisdiction of the Office of the Basic Education Commission. The instrument for data collection was learning happiness scale. The data were analyzed by the SPSS for windows, MULTILOG, SIBTEST and the Microsoft Office Excel. The findings were as follows.1) The learning happiness scale had four dimensions: quality of teaching; the emotion expression; school’s teaching support and happy learning and instrument which factors loading score were among 0.487-0.749. 2) The learning happiness scale consisted of 31 indicators and 31 items which had IOC between 0.8 -1.0 and alpha coefficient = 0.959. 3) The analysis with IRT showed that item difficulty were 1.27 to 2.23 and item discrimination were -2.22 to +2.36 4) The result of Difference Item Function analysis revealed the DIF in sex (p<0.05) for 9 items. 5) The norm for male and female, most high student had score on learning happiness scale between T[subscript 77.50] – T[subscript 116.00] and (P[subscript 50.00] – P[subscript 74.99]).